Biological resources and migration: with 23 tables ; [the Conference and OECD Workshop were organized at the Philipps University in Marburg (Germany)] - Werner, Dietrich (Springer, 2004)
Migration is a global and ubiquitous phenomenon. A large percentage of our cultivated land in industrialized as well as in developing countries are covered with migrated or introduced plants. But also in natural habitats and communities, migration of animals, plants and microorganisms plays a key role in the functioning or threat to the present ecosystems. The special feature of this book is that all forms of migration - be it plant, microbial, animal or human - and their mutual impact are covered in detail. It is estimated that during the next twenty years more than one billion people will migrate from rural areas to urban districts worldwide, forced by deteriorating biological resources and with enormous consequences on the functioning of both ecosystems and such central economic areas such as trade, transport and tourism. The contributions in this book are the result of an innovative International Conference and OECD Workshop aimed at triggering off the interdisciplinary dialogue between natural scientists and socioeconomists. TOC:The Gene Ricepool and Human Migrations.- Movement of Rice Germplasm Around the World.- Potential for Gene Flow from Cultivated Wheat to Weedy Relatives in the Great Plains of North America.- Humans, Climate, and Plants: the Migration of Crested Wheatgrass and Smooth Bromegrass to the Great Plains of North America.- Biogeography, Local Adaptation, Vavilow, and Genetic Diversity in Soybean.- Migration of a Grain Legume, Phaseolus vulgaris, in Europe.- Forest History in Europe.- Forest Biologicial Resources in the Amazon Basin.- Migration of Knowledge Lead to the Floristic Development in Myanmar.- Tracking Parasitoids at the Farmland Field Scale Using Microsatellite Markers.- Interhemispheric Transport of Viable Fungi and Bacteria From Africa to the Caribbean With Soil Dust.- Be a Virus, See the World.- Species Delineation and Biogeography of Symbiotic Bacteria Associated to Cultivated and Wild Legumes.- Micro-Spatial Distribution of Bacteria in Rhizosphere.- Colonization of Some Polish Soils by Azotobacter spp. at the Beginning and at the End of the 20th Century.- Estimation of Biotic and Abiotic Factors that Affect Migration of Rhizobia.- Indigenous Strains of Rhizobia and Their Performance in Specific Regions of India.- Migration of Aquatic Invertebrates.- Migration of Fishery Resources in the Worldś Oceans.- Migration of Marine Mammals.- The "Global Register of Migratory Species"- First Results of Global GIS Analysis.- Coup ...
Literaturangaben
Keywords: Konferenzschrift -- Marburg; Konferenzschrift; Biologische Ressourcen; Migration; Ökosystem